2020
DOI: 10.3390/ijms21155428
|View full text |Cite
|
Sign up to set email alerts
|

Moderate High Caloric Maternal Diet Impacts Dam Breast Milk Metabotype and Offspring Lipidome in a Sex-Specific Manner

Abstract: Lactation is a critical period during which maternal sub- or over-nutrition affect milk composition and offspring development that can have lasting health effects. The consequences of moderate high-fat, high-simple carbohydrate diet (WD) consumption by rat dams, during gestation and lactation, on milk composition and offspring blood lipidome and its growth, at weaning, were investigated by using a comprehensive lipidomic study on mass-spectrometric platform combined to targeted fatty- and free amino-acids anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Moreover, it is noteworthy that the plasma TG profile in REV-pups, also in terms of double bounds, was fully normalized to that of CON-pups, in both males and females. This is in accordance with the results obtained by Alexandre-Gouabau et al, [12] in which the lower content of TG with saturated medium-chain FA, together with the higher content of TG with unsaturated long-chain FA, in the milk of dams fed with WD during gestation and lactation, were associated to a blood lipidome of their offspring with reduced levels of TG containing saturated FA. Thus, our results suggest that the plasma TG composition in pups during lactation is reflecting both the maternal diet during this period and the metabolic status of the animals already at this early age.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, it is noteworthy that the plasma TG profile in REV-pups, also in terms of double bounds, was fully normalized to that of CON-pups, in both males and females. This is in accordance with the results obtained by Alexandre-Gouabau et al, [12] in which the lower content of TG with saturated medium-chain FA, together with the higher content of TG with unsaturated long-chain FA, in the milk of dams fed with WD during gestation and lactation, were associated to a blood lipidome of their offspring with reduced levels of TG containing saturated FA. Thus, our results suggest that the plasma TG composition in pups during lactation is reflecting both the maternal diet during this period and the metabolic status of the animals already at this early age.…”
Section: Discussionsupporting
confidence: 93%
“…[ 10 ] Thus, intervention studies in rodents have shown that the intake of an obesogenic diet during the perinatal period negatively affects the structure and function of the mammary gland and therefore the composition of milk, [ 11 ] including altered metabolism‐regulating hormones and fatty acids (FA) profiles. [ 12,13 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies did not find any relation between total protein content in mature breast milk and maternal total energy or total protein intake, 33 as well as between total protein content in breast milk and the dietary content of carbohydrates and fat 26 . In rodent models, milk protein content was also found to be unaffected in animals fed, during gestation and lactation alone, with low protein 34,35 and with high energy 36 diet.…”
Section: Milk Composition Is Affected By Maternal Metabolic Status and Dietmentioning
confidence: 87%
“…Today, a number of epidemiological studies and animal model studies suggest that environmental factors in embryonic, fetal, neonatal, and early childhood periods are associated with health and disease in adulthood and old age, including the risk of developing chronic diseases, supporting the DOHaD theory [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. For example, in cases of food deprivation during pregnancy, the fetus acquires an energy-saving constitution in anticipation of the environment after birth, in which nutrient intake may be insufficient [ 78 ].…”
Section: Dohad Theorymentioning
confidence: 99%